2013
DOI: 10.1089/tmj.2013.0009
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Self-Monitoring Web Technology Acceptance and Use in an e-Health Weight-Loss Trial

Abstract: The adapted acceptance measures showed acceptable psychometric properties and significant associations with actual Web site use, which correlated with weight loss. Better understanding of technology acceptance and use in e-health weight-loss interventions may improve participant adherence and outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 20 publications
0
16
0
3
Order By: Relevance
“…Por otra parte, entre los estudios de calidad metodológica media, tres de ellos (31,(33)(34)(35) indican diferencias significativas en cuanto a la pérdida de peso en el grupo de intervención de coaching comparado con el grupo control. Sin embargo, en el estudio The Change Program (32) las diferencias no son significativas quizás debido a que el grupo control incorpora también técnicas de coaching.…”
Section: Discusión Valoración De Los Resultadosunclassified
See 1 more Smart Citation
“…Por otra parte, entre los estudios de calidad metodológica media, tres de ellos (31,(33)(34)(35) indican diferencias significativas en cuanto a la pérdida de peso en el grupo de intervención de coaching comparado con el grupo control. Sin embargo, en el estudio The Change Program (32) las diferencias no son significativas quizás debido a que el grupo control incorpora también técnicas de coaching.…”
Section: Discusión Valoración De Los Resultadosunclassified
“…y por otra qué formación en coaching ha recibido. En algunos estudios (27)(28)(29)31,(33)(34)(35)40,41,(54)(55)(56) no se aporta suficiente información que especifique la formación de coaching que reciben los profesionales que aplican la intervención, por lo que no podemos garantizar que ésta exista. Por otra parte, en un 18% de los estudios incluidos en nuestra revisión (28,29,49,56,58,64,65) no se comenta nada al respecto de la formación académica del personal que aplica coaching, aspecto que impide saber los conocimientos técnicos que posee.…”
Section: Capacitación O Formación De Los Profesionalesunclassified
“…Although self‐monitoring itself, such as keeping a food journal, has been shown to be effective in helping with weight loss in other studies , more detailed tracking of dietary intakes and physical activity was typically employed. Some studies with technology‐assisted self‐monitoring have also shown effectiveness . Regardless, typical self‐monitoring data are not objective and are subject to report bias.…”
Section: Discussionmentioning
confidence: 99%
“…60 Innovative approaches to increase patients' adherence to recommendations are required. The use of mobile health technologies and telecommunication has rapidly been integrated into the health-care delivery system for the management of chronic illnesses (eg, hypertension, 61 weight loss, 62 and diabetes 63 ) and may prove useful for improving adherence in patients with CF by allowing adolescents to directly call their CF health-care team and by promoting safe social interactions and peer support. 4 The results of this systematic review should be considered in light of the following limitations.…”
Section: Discussionmentioning
confidence: 99%